Small Ruminants Farming in Pakistan - Ishaq, Muhammad; Haq, Zahoor ul (Annals of Arid Zone, 2016)
Livestock play an important role in the rural economy of Pakistan. It produces food, enhances crop production. generates cash income, provides year-round employment. spreads risk and provides fuel and transport. In the mountainous. rain fed, saline affected and desert areas of Pakistan, where crop production is uncertain, fariners subsist on livestock farming. Sheep. and goats are reared as a subsidiary source of livelihood in these areas and utilized for milk, ~utton, skin and wool production. The growth pattern of goat population in Pakistan shows an annual increase of 3.04% per year. However, sheep numbers declined and a swift decline occurred during 1994-95 and the subsequent years, due to prolonged drought. Meat (mutton) production from both sheep and goats in the country has generally increased rapidly over the last two decades at a rate of 3.67% to meet the demand of ever growing population. However, a sharp decrease in mutton production has been observed during the prolonged drought of mid-1990s when hundred of livestock especially sheep died. On the other hand, high emphasis on wool production may lead to 'a reduction in mutton produced per head as both ewes and wethers that would otherwise be sent to slaughter may be kept for wool productio